High-Reliability Dynamic-Threshold Source-Side Injection for 2-Bit/Cell With MLC Operation of Wrapped Select-Gate SONOS in NOR-Type Flash Memory - Wang, Kuan-Ti; Chao, Tien-Sheng; Wu, Woei-Cherng; Yang, Wen-Luh; Lee, Chien-Hsing; Hsieh, Tsung-Min; Liou, Jhyy-Cheng; Wang, Shen-De; Chen, Tzu-Ping; Chen, Chien-Hung; Lin, Chih-Hung; Chen, Hwi-Huang (My University, 2010)
For the first time, a high-performance (tau(PGM) = 200 ns/tau(ERS) = 5 ms) cell with superior reliability characteristics is demonstrated in a NOR-type architecture, using dynamic-threshold source-side injection (DTSSI) in a wrapped select-gate silicon-oxide-nitride-oxide-silicon memory device, with multilevel and 2-bit/cell operation. Using DTSSI enables easy extraction of the multilevel states with a tight V(TH) distribution, a nearly negligible second-bit effect, superior endurance characteristics, and good data retention.
Keywords: Flash memory; multilevel states in a cell (MLC); NOR; silicon-oxide-nitride-oxide-silicon (SONOS)